Diversity of urban street tree communities in Semarang District, Indonesia - ARDHIAN ABDUL MADJID; ARDITA AYU WULANDARI; ASFI DZIHNI; MARIO PINTOR DAVID SIMANJUNTAK; SAFIRA CHAIRUNISA; ARU DEWANGGA; WIDHI HIMAWAN; INOCENCIO E. BUOT JR; AHMAD DWI SETYAWAN (Nusantara Bioscience, 2025)
Abstract. Madjid AA, Wulandari AA, Dzihni A, Simanjuntak MPD, Chairunisa S, Dewangga A, Himawan W, Buot Jr IE, Setyawan AD. 2025. Diversity of urban street tree communities in Semarang District, Indonesia. Nusantara Bioscience 17: 337-353. Roadside vegetation plays an important role in maintaining ecological functions, microclimate regulation, and environmental quality in rapidly urbanizing tropical landscapes. This study examined the diversity, composition, and functional structure of urban street trees across five major 10-km roadside corridors in Semarang District, Central Java, Indonesia. Field surveys conducted in September 2024 recorded 2,091 individuals representing 53 species, 47 genera, and 26 families, and classified into functional categories based on ecological and management attributes. Species richness and abundance varied markedly among routes. The Bandungan-Kaloran corridor showed the highest richness and stability, while the Ungaran-Cangkiran corridor exhibited the strongest species dominance, and the Semarang-Bawen corridor had the lowest richness. Three species-Swietenia mahagoni, Polyalthia longifolia, and Mangifera indica-emerged as district-wide dominants. Functional composition was heavily skewed toward Ornamental Plant (OP) and Timber Plants (TP), with Frugivory-supporting species (Fr) providing secondary ecological roles. Diversity indices (Shannon, Simpson, Margalef, and Evenness) revealed substantial spatial heterogeneity: peri-urban routes showed balanced community structures, whereas highly built-up corridors exhibited low diversity and high dominance. These patterns highlight the influence of urbanization intensity, planting space limitations, and disturbance pressure on roadside vegetation structure. These findings highlight the need for more diversified and functionally balanced street tree planting strategies to enhance the sustainability and resilience of urban green infrastructure in Semarang District and other rapidly developing tropical cities.